The Image of Women in Cross-cultural Perspective: The Case of Dunhuang Mural Paintings - Guo, Wei (International Journal of Social Sciences and Public Administration, 2024)
This paper analyses the images of women in Dunhuang murals and their status and role in society in the context of Chinese history, culture and religion, and explores the phenomenon of cross-cultural intermingling in these murals and the influence of foreign cultures on these images in the context of foreign cultural elements and globalisation. To obtain background information about Dunhuang murals through the study of historical documents, Buddhist classics and Dunhuang research materials. Systematically analyses the murals of Guanyin Bodhisattva, the statue of the feeder, the flying nymphs and the legend of the deer maiden, and explores how these images of women incorporate elements of foreign cultures from India, Persia, and Central Asia, demonstrating the phenomenon of cross-cultural intermingling on the Silk Road. The study demonstrates that the images of women in Dunhuang murals demonstrate the status and important role of women in ancient societies, provide rich cultural and historical information for future generations, promote historical understanding and modern recognition of women's power, shed light on the rise of women in ancient societies as well as the fusion of Chinese and foreign cultures millennia ago, and provide invaluable historical experience and insights for women's empowerment and cross-cultural understanding in modern societies.